The Color of Sin - Sherman, Gary D.; Clore, Gerald L. (Psychological Science, 2009)
Three studies examined automatic associations between words with moral and immoral meanings and the colors black and white. The speed of color naming in a Stroop task was faster when words in black concerned immorality (e.g., greed), rather than morality, and when words in white concerned morality (e.g., honesty), rather than immorality. In addition, priming immorality by having participants hand-copy an unethical statement speeded identification of words in the black font. Making immorality salient in this way also increased the moral Stroop effect among participants who had not previously shown it. In the final study, participants also rated consumer products. Moral meanings interfered with color naming most strongly among those participants who rated personal cleaning products as especially desirable. The moderation of the moral Stroop effect by individual differences in concerns about personal cleanliness suggests that ideas about purity and pollution are central to seeing morality in black and white.